Availability of integrated care for co-occurring substance abuse and psychiatric conditions. - Ducharme LJ; Knudsen HK; Roman PM (Community Mental Health Journal, 2006)
The co-occurrence of psychiatric conditions and substance abuse presents significant challenges for behavioral healthcare providers. The need for integrated care has received substantial recent attention from clinical, research, and funding entities. However, the availability of integrated care has been low, carrying potential adverse implications for quality of care and treatment outcomes. This article describes the prevalence and key correlates of the availability of integrated care for co-occurring conditions within public and private-sector addiction treatment programs. Several organizational attributes, caseload characteristics, and service provision patterns were associated with the availability of integrated care.